Development Strategy of Taman Hutan Raya (Tahura) Sultan Syarif Hasyim Sustainable Management - Suhartono Suhartono; Aslim Rasyad; Syaiful Hadi (Program Pascasarjana Universitas Riau, 2017)
Tahura Sultan Syarif Hasyim can become the center of ecotourism attraction because the location is close to Pekanbaru as the capital city of Riau Province and its high diversity of flora and fauna species. The nature of this landscape is very potensial to be utilized as an object of ecoturism with beautiful forest panorama. The purpose of this research is to formulate a sustainable development strategy of Tahura SSH management plan. This research was conducted by using survey method. To obtain primary data through observations and deep interview and secondary data through literature, thesis, journal and report, maps and related statistical data. The result of the research obtained alternative collaborative and interactive ecotourism development strategies whose management involves government, entrepreneur and societies (local communities, NGOs, visitors). This strategy is expected to achieve the objectives of Tahura as a natural conservation area, both for plants and animals that are used for the public interest, researches, science and education as specified by the regulations in the establishment of Tahura SSH.